Sofosbuvir and risk of estimated glomerular filtration rate decline or end‐stage renal disease in patients with renal impairment. Issue 9 (2nd March 2022) - Sulkowski, Mark; Telep, Laura E.; Colombo, Massimo; Durand, Francois; Reddy, K. Rajender; Lawitz, Eric; Bourlière, Marc; Cheinquer, Nelson; Scherbakovsky, Stacey; Ni, Liyun; Force, Lindsey; Ramroth, Heribert; et al.
Summary: Background: Sofosbuvir, a prodrug nucleoside inhibitor of hepatitis C virus, has a predominant circulating metabolite that is renally eliminated. Whether sofosbuvir is associated with chronic kidney disease (CKD) progression is not well understood. Methods: We performed a retrospective analysis of patients with estimated glomerular filtration rate (eGFR) 30–89 mL/min/1.73 m 2 treated with sofosbuvir in 76 Phase 2/3 registrational trials. We evaluated eGFR at each study visit. Separately, we performed a retrospective analysis of an administrative claims database (IQVIA PharMetrics Plus™) to compare the risk of incident end‐stage renal disease (ESRD) associated with the use of sofosbuvir or non‐sofosbuvir regimens among patients with CKD using propensity score methods. Exposure, CKD status and outcomes were determined using diagnosis and medication claim codes. Cox proportional hazards methods were used to estimate ESRD risk. Results: Among 4642 trial participants with baseline stage 2 CKD (eGFR 60–89 ml/min/1.73 m 2 ) and 682 trial participants with stage 3 CKD (eGFR 30–59 ml/min/1.73 m 2 ) mean (SD) eGFR improved from baseline to 4 weeks post‐treatment (+0.7 [9.3] and +2.6 [8.8] ml/min/1.73 m 2, respectively; p < 0.001 each). In the second analysis, among 2042 patients with CKD receiving sofosbuvir‐based regimens compared to 431 receiving non‐sofosbuvir‐based regimens, after adjusting for baseline covariates and weighting based on treatment propensity scores, there was no significant difference in risk of ESRD (adjusted HR = 0.85, 95% CI: 0.51–1.42). Conclusions: Clinical trial participants with CKD did not experience worsening eGFR during sofosbuvir‐based treatment, and sofosbuvir was not associated with an increased risk of ESRD in patients with CKD in a nationally‐representative administrative claims database. Abstract : Sofosbuvir and risk of estimated glomerular filtration rate decline or end‐stage renal disease in patients with renal impairment.